(untitled) (Global Journal of Science Frontier Research, 2023)
In a world addicted to crude oil US control over Saudi Arabia s oil exports is a non-lethal weapon of mass destruction Due to resistance by politicians bankers and investors to writing-off trillions of dollars in fossil fuel assets global greening will evolve over two stages The first stage will likely materialize between 2030 and 2040 as the world s two biggest oil importers China and Europe replace the internal combustion engine with the electric vehicle to enhance their national security The first stage will cause most global demand for oil to disappear with serious consequences for the economies and the political map of the Middle East The second stage will evolve over a century or more It will abandon coal and natural gas and enhance environmental protection